2012
DOI: 10.1186/1476-7961-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Clara cell protein in nasal lavage fluid and nasal nitric oxide - biomarkers with anti-inflammatory properties in allergic rhinitis

Abstract: BackgroundClara cell protein (CC16) is ascribed a protective and anti-inflammatory role in airway inflammation. Lower levels have been observed in asthmatic subjects as well as in subjects with intermittent allergic rhinitis than in healthy controls. Nasal nitric oxide (nNO) is present in high concentrations in the upper airways, and considered a biomarker with beneficial effects, due to inhibition of bacteria and viruses along with stimulation of ciliary motility. The aim of this study was to evaluate the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
(41 reference statements)
1
20
0
1
Order By: Relevance
“…The results of one study concerning the role of CC16 in nasal inflammation in patients with PAR showed a positive correlation between the nasal fluid concentrations of CC16 and nasal production of nitric oxide (NO) [15]. This study also demonstrated a negative correlation between these biomarker concentrations in nasal secretions and the levels of mucosal infiltration by mast cells [15].…”
Section: Discussionmentioning
confidence: 54%
“…The results of one study concerning the role of CC16 in nasal inflammation in patients with PAR showed a positive correlation between the nasal fluid concentrations of CC16 and nasal production of nitric oxide (NO) [15]. This study also demonstrated a negative correlation between these biomarker concentrations in nasal secretions and the levels of mucosal infiltration by mast cells [15].…”
Section: Discussionmentioning
confidence: 54%
“…Therefore, reducing the inflammatory response is regarded as the primary interference measure for COPD patients. It is well-known that CC16 is a secretory protein with anti-inflammatory characteristics (21). Reduced levels of CC16 in the bronchial epithelium or sputum supernatants of COPD patients may be a contributing factor in airway inflammations (4,22).…”
Section: Discussionmentioning
confidence: 99%
“…A CC16 é um biomarcador de alto interesse nas doenças das vias aéreas e pode difundir passivamente do trato respiratório para o sangue, sendo inclusive excretada pelo trato urinário. CC16 está atribuída a um papel protetor contra o estresse oxidativo e inflamação do trato respiratório (IRANDER et al, 2012).…”
Section: Proteína Das Células De Claraunclassified